9(x-3)/3=3(x+5)/9

Simple and best practice solution for 9(x-3)/3=3(x+5)/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-3)/3=3(x+5)/9 equation:



9(x-3)/3=3(x+5)/9
We move all terms to the left:
9(x-3)/3-(3(x+5)/9)=0
We calculate fractions
9x/()+(-(3(x+5)*3)/()=0
We calculate terms in parentheses: +(-(3(x+5)*3)/(), so:
-(3(x+5)*3)/(
We multiply all the terms by the denominator
-(3(x+5)*3)
We calculate terms in parentheses: -(3(x+5)*3), so:
3(x+5)*3
We multiply parentheses
9x+45
Back to the equation:
-(9x+45)
We get rid of parentheses
-9x-45
Back to the equation:
+(-9x-45)
We get rid of parentheses
9x/()-9x-45=0
We multiply all the terms by the denominator
9x-9x*()-45*()=0
We add all the numbers together, and all the variables
9x-9x*()=0

See similar equations:

| 110=2(7=2w)=2w | | 4(7-2n)+5n=3(5n+21)+1 | | 16/7x=8/21 | | -1.4x=4(x+2.19) | | (x+5)(x+7)=(x-3)(x-12) | | 7(x-2)-4x=110 | | 7-2n=5n+21 | | 25/3=y | | -3(5t-4)+2t=4t-9 | | -4(5t-4)+5t=4t-5 | | 124=34m | | 6-4n=-6 | | 8v-4=5+8v | | 8v-8v=5-3 | | -2y-11=3y+19 | | (x+4)=x+(x+2)+(x+4)-2 | | 1/3=m+1/4 | | 2.5t+7.7=4.7 | | 2.5t+4.7=7.7 | | 7/8x-9/16=-1/2 | | 3y-7+y+47=5y+40-3y | | (x+1)=2x+15 | | x=3(-x)+68 | | 6-8y=70 | | 3+2(8x-9)=5x-26 | | 6-8y=80 | | 6=x/4+9 | | 2n^2+n=300 | | −4.75=z/2 | | 2.71^4x=20 | | 6k+k+14=56 | | -6=2g |

Equations solver categories